Fashion in turmoil: impact of the COVID-19 pandemic on Finland's textile and fashion industry. Issue 1 (8th December 2023) - Haukkala, Teresa; Niinimäki, Kirsi; Turunen, Linda Lisa Maria
Abstract: With continuing climate change, consumers are reconsidering their fashion-consumption habits and clothing and apparel businesses are critically examining their industrial practices. The coronavirus pandemic can be considered a turning point as it has significantly affected the textile and fashion industry. By applying path-dependence theory to analyze developments in the textile and fashion industry in Finland, this study investigates prior pivotal moments to better understand how crises can provide possibilities for transformation. We first provide a historical review that aims to identify external shocks as major transitional events and examines their implications for short- and long-term trends. The study then analyzes the changes triggered by COVID-19 in the textile and fashion industry using empirical data collected from Finnish companies. The study reveals that the pandemic forced some firms to introduce several changes into their practices as part of efforts to survive, including innovations at all levels of design and manufacturing as well as new ways of managing sales and marketing. In addition, the crisis has been an opportunity to take steps toward societal and environmental transformation through more open and responsible business models involving a shift to local or close-by production to reduce environmental impact, to secure decent factory-working conditions, and to engage customers to reduce their consumption. The article concludes by considering issues relevant to the future of this industry during the post-pandemic period.